Electromagnetic flux modeling of ac field over planar microarray dot electrodes used in dielectrophoretic lab-on-chip device - Azaman, A. (2012)
Introduction: Lab-on-chip devices have been proven to be advantageous in terms of selective collection, manipulation and separation of cells and particles. Numerous physical methods have been employed in the development of such devices, and alternating current (AC) electrokinetics was one of the chosen techniques due to its selectivity, efficacy, noninvasiveness, and low fabrication costs. Recently it has been shown that, by employing a specific AC electrokinetics technique called dielectrophoresis, it was possible to fabricate an addressable microarray dots in creating axisymmetrical AC fields over a planar microelectrode within a chamber containing the cell sample. Each of these dots received different input frequency values in order to create the required field with specific gradient strength, thus enabling dielectrophoretic experiments to take place in rapid succession. The objective of this study is to simulate the generation of the said electromagnetic fluxes over the microarray dots using finite element methods. Materials and Methods: Three different materials, namely copper, gold, and indium tin oxide were used, and simulated at different input frequencies and environment. Results and Discussion: The results indicate that the generated AC electric fields are satisfactory in creating the required DEP effects within a chamber height of 200 μm. Different electrode materials and environment produced no significant difference (p>0.05) in terms of the maximum and minimum electrical gradient strengths. Further investigation with regards to the optimal distance in between the dots is warranted in order to create consistent dielectrophoretic effects with optimal particle density.